Favourite stories of courageous girls - Illustrated by Lawson, Nan (Great Britain Hodder Children's Books, 2019)
This wonderful anthology features the stories of some of the best-loved heroines in children's books. From Jo March who sells her hair to raise money for her family, to George's single-minded commitment to protecting her island in The Famous Five to Bobbie's quick-thinking action that prevents a train crash in The Railway Children, these girls demonstrate courage beyond their years. Each of the 24 chapters contains an introduction about the courageous girl featured and a satisfying extract from the original book. These fictional heroines will inspire young readers with their stories of expectations defied, fears faced and obstacles overcome. This collection is also bound to tempt readers to discover these classic novels for themselves.Classic novels featured include Little Women, Anne of Green Gables, Five on a Treasure Island, The Railway Children, Jane Eyre, A Little Princess, Pollyanna and The Wizard of Oz, as well as beloved fairy tales from diverse cultures such as The Snow Queen, Kate Crackernuts and White Chrysanthemum.
Keywords: Children Fiction